Judge's Discretion and Independence as a Basis for Justice Reform in Peru - Morales Godo, Juan (2009)
This paper intends to study the importance of having as a basis the discretion and independence of the judge in the panorama of justice reform in Peru, focusing on the vision posed by neo-constitutionalism, the relevance of legal argumentation and judicial decision and, the relationship between judicial discretion and the just decision. In the first part, a brief introduction to the reform of justice and the change of paradigm towards neo-constitutionalism is offered. After that, the new objectives and practices that neo-constitutionalism seeks within the framework of a Constitutional State of Law are developed. In the third part, the relationship between judicial decision and legal argumentation is analyzed, highlighting it as relevant with the arrival of neo-constitutionalism. After that, a comparison is made between the judicial discretion of the judge in a legalistic State of law and a constitutional State of law, highlighting the power of the judge. Finally, the importance of judicial independence and legal argumentation in the Constitutional State of Law is developed, all within the framework of the search for pillars for a justice reform in Peru.